HUBUNGAN TINGKAT KECUKUPAN NATRIUM DAN KALIUM DENGAN HIPERTENSI PADA LANJUT USIA UNIT PELAKSANA TEKNIS DAERAH PELAYANAN SOSIAL LANJUT USIA TRESNA WERDHA LAMPUNG TAHUN 2021 - Mitha Hamidah Haris Alhamidi; Sona Utari; Desti Ambar Wati; Riska Nur Suci Ayu; Alifiyanti Muharramah (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2022)
Background: Hypertension or high blood pressure is a condition where a person's blood pressure is above normal. Where is the result of the preliminary pre survey conducted by the researcher to the UPTD for Elderly Social Services, Tresna Werdha. data obtained from elderly patients with hypertension at the UPTD of Tresna Werdha Social Panti Lampung as many as 21 elderly (25.30%). Objective: The purpose of this study was to determine the corelation between the adequacy of sodium and potassium levels with hypertension in the elderly, the technical implementing unit for the elderly social service area Tresna Werdha Lampung in 2021. Method: The design used in this study is a quantitative research using a cross sectional research design. The population in this study were 80 elderly people in the Regional Technical Implementation Unit for Elderly Social Services Tresna Werdha Lampung. Bivariate analysis in this study using Spearman's Rank Test.. Results: The results of this study obtained hypertension 1 as many as 18 people (85.71%), the level of potassium adequacy for 21 elderly was lacking (100%), and sodium adequacy level for 21 elderly was lacking (100%). Conclusion: there was no corelatiom between potassium adequacy level and hypertension (p = 0.102) and there was no corelation between sodium adequacy level and hypertension (p = 0.541).